Anode-free solid-state battery with quasi-solid lithium gel layer

JP7644986B2Active Publication Date: 2025-03-13TERAWATT TECHNOLOGY INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022506083
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-29
Filing Date
2020-07-28
Publication Date
2025-03-13
Estimated Expiration
2040-07-28

AI Technical Summary

Benefits of technology

【0005】 【0005】 このような方法の実施形態は、以下の特徴の1つ又は複数を含み得る。リチウムゲルセパレータ層を作ることは、第1の接着層を骨格に取り付けることを含んでもよい。本方法は、第2の接着層を骨格に取り付けることを含んでもよい。本方法は、液体電解質を骨格に浸透させることを含んでもよい。液体電解質は、リチウム塩と、溶媒と、少なくとも1つの添加剤とを含んでもよい。少なくとも1つの添加剤は、ポリマー及び架橋剤を含んでもよい。熱を加えることにより、液体電解質がゲルになり得る。デンドライト防止層の存在が、リチウムイオンがアノード電流コレクタ層上に堆積するためのエネルギーに関して、核形成バリアを減少させ得る。デンドライト防止層は、0.05マイクロメートル~10マイクロメートルの厚さでもよい。本方法は、ジグプレス内で可撓性パウチセルを圧縮することをさらに含んでもよい。本方法は、ジグプレス内で積層電池スタックの充電及び放電を行うことをさらに含んでもよい。デンドライト防止層は、カーボンブラック、アセチレンブラック、ケッチェンブラック、銀、亜鉛、金、ビスマス、スズ、フッ化ポリビニリデン(PVDF)、ポリイミド(PI)、ポリアクリル酸(PAA)、及びカルボキシメチルセルローススチレンブタジエンゴム(CMC-SBR)から成る群から選択される1つ又は複数の材料を含んでもよい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644986000002
    Figure 0007644986000002
  • Figure 0007644986000003
    Figure 0007644986000003
  • Figure 0007644986000004
    Figure 0007644986000004
Patent Text Reader

Abstract

In various embodiments, a dendrite-preventing anode-free solid-state battery (SSB) is presented. The SSB may include a cathode layer, an anode current collector layer, and a lithium gel separator layer between the cathode layer and the anode current collector layer. An anti-dendrite layer may be present and located between the lithium gel separator layer and the anode current collector layer. The anti-dendrite layer can help prevent the formation of dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] During charging of a lithium-ion battery, lithium ions migrate from the battery's cathode to the battery's anode through a separator located between the cathode and anode. Through a process called intercalation, the lithium ions become inserted into the material that functions as the anode. Also during this charging process, the lithium ions may plate onto the surface of the anode opposite the separator. The nucleation energy associated with the anode may encourage the lithium ions to plate onto other lithium already plated on the anode (rather than plating into a generally uniform film across the surface of the anode). These pools of lithium may form dendrites. Dendrites may be protrusions of lithium metal that extend away from the surface of the anode toward the separator. Over time (e.g., through multiple charge and discharge cycles), the dendrites may grow to such a length that they penetrate the separator and directly electrically connect the cathode to the anode (i.e., a short circuit). Such an electrical connection may have serious unintended consequences, such as destruction of the battery and, in some cases, overheating and fire. Summary of the Invention [Means for solving the problem]

[0002]

[0002] Various embodiments relating to dendrite-preventing anode-free solid-state batteries are described. In some embodiments, dendrite-preventing anode-free solid-state batteries are described. The battery may include a cathode layer. The battery may include an anode current collector layer. The battery may include a lithium gel separator layer between the cathode layer and the anode current collector layer. The battery may include an anti-dendrite layer located between the lithium gel separator layer and the anode current collector layer. The anti-dendrite layer can prevent the formation of dendrites.

[0003]

[0003] Embodiments of such devices may include one or more of the following features: The lithium gel separator layer may include a first adhesive layer. The lithium gel separator layer may include a second adhesive layer. The lithium gel may include a lithium gel layer located between the first adhesive layer and the second adhesive layer. The lithium gel separator layer may include a scaffolding material, a salt, a solvent, and at least one additive. The at least one additive may include a polymer and a crosslinker. The first adhesive layer and the second adhesive layer may include a lithium conductor ceramic. The presence of the anti-dendrite layer may reduce the nucleation barrier for the energy for lithium ions to deposit on the anode current collector layer. The anti-dendrite layer may be 0.05 micrometers to 10 micrometers thick. The anti-dendrite layer may include one or more materials selected from the group consisting of carbon black, acetylene black, ketjen black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR). A first amount of adhesion between the anti-dendrite layer and the anode current collector layer may be less than a second amount of adhesion between the anti-dendrite layer and the lithium gel separator layer. The anode current collector layer may be copper. The device may further include an aluminum cathode current collector.

[0004]

[0004] In some embodiments, a method for making an anti-dendrite anode-free solid-state battery is described. The method may include depositing an anti-dendrite layer on an anode current collector layer. The method may include making a lithium gel separator layer. The method may include stacking a cathode current collector layer on a cathode layer. The method may include stacking a lithium gel separator layer between the anti-dendrite layer and the cathode layer, thereby making a stacked battery stack of a cathode current collector layer, a cathode layer, a lithium gel separator layer, an anti-dendrite layer, and an anode current collector layer. The method may include packaging the stacked battery stack in a flexible pouch cell. The method may include applying heat and pressure to the stacked battery stack in the flexible pouch cell.

[0005]

[0005] An embodiment of such a method may include one or more of the following features. Creating a lithium gel separator layer may include attaching a first adhesive layer to a scaffold. The method may include attaching a second adhesive layer to the scaffold. The method may include infiltrating a liquid electrolyte into the scaffold. The liquid electrolyte may include a lithium salt, a solvent, and at least one additive. The at least one additive may include a polymer and a crosslinker. The liquid electrolyte may gel by applying heat. The presence of an anti-dendrite layer may reduce the nucleation barrier for the energy for lithium ions to deposit on the anode current collector layer. The anti-dendrite layer may be 0.05 micrometers to 10 micrometers thick. The method may further include compressing the flexible pouch cell in a jig press. The method may further include charging and discharging the laminated battery stack in the jig press. The anti-dendrite layer may comprise one or more materials selected from the group consisting of carbon black, acetylene black, ketjen black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR). [Brief description of the drawings]

[0006] [Figure 1] 1 shows an embodiment of a layer stack for an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer. [Diagram 2]

[0007] 1 illustrates another embodiment of a layer stack for an anode-free solid-state battery having multiple lithium gel separator layers and multiple anti-dendrite layers. [Figure 3A]

[0008] 1 illustrates one embodiment of a lithium gel separator layer formed using heat. [Figure 3B]

[0009] 1 illustrates one embodiment of a method for making a lithium gel separator layer. [Figure 4]

[0010] 1 illustrates one embodiment of a method for manufacturing a pouch-type battery cell including an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer. [Diagram 5]

[0011] 1 illustrates one embodiment of a cylindrical battery press system. [Figure 6A]

[0012] 1 illustrates one embodiment of a method for making a cylindrical dendrite-preventing anode-free solid-state battery. [Figure 6B]

[0012] One embodiment of a method for making a cylindrical dendrite-preventing anode-free solid-state battery is presented. [Figure 7]

[0013] 1 illustrates one embodiment of a layer stack for an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interfacial bonding layer. [Figure 8]

[0014] 1 illustrates one embodiment of a layer stack for an anode-free solid-state battery, showing the relative amount of adhesion between the various layers. [Figure 9]

[0015] 1 illustrates one embodiment of a layer stack of an anode-free solid-state battery during charging, where lithium is deposited on an interfacial bonding layer. [Figure 10]

[0016] 1 illustrates one embodiment of a method for manufacturing a pouch-type battery cell including a solid-state battery having a lithium-gel separator layer, an anti-dendrite layer, and an interfacial bonding layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007]

[0017] The introduction of an anti-dendrite layer in combination with a lithium gel separator layer can inhibit dendrite growth without significantly increasing the thickness of the battery cell. The anti-dendrite layer may be coated directly onto the anode current collector of an anode-free solid-state battery (SSB). In an anode-free SSB, the anode current collector, which may be a copper foil, may effectively function as both the anode and the anode current collector. The anti-dendrite layer may reduce the nucleation energy required for lithium ions to deposit as lithium metal on the surface of the anode current collector in contact with the anti-dendrite layer. Instead of the lithium ions tending to plate onto the lithium metal already plated on the surface of the anode current collector (thus causing pooling that can lead to dendrites), the lithium may tend to deposit in a nearly uniform film across the surface of the anode current collector.

[0008]

[0018] The dendrite prevention layer may be in direct contact with the lithium gel separator layer. The lithium gel separator layer may perform multiple functions. First, the lithium gel separator layer may function as a solid electrolyte to facilitate the movement of lithium ions between the cathode and the anode. The lithium gel separator layer may also act as a separator to prevent direct electrical connection between the cathode and the anode. The lithium gel separator layer may further have features that further inhibit the growth of dendrites.

[0009]

[0019] Further details regarding such and further embodiments are provided in conjunction with the drawings. Figure 1 shows one embodiment of a layer stack 100 of an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer. The layer stack 100 can include a cathode current collector 110, a cathode 120, a lithium gel separator layer 130, an anti-dendrite layer 140, and an anode current collector 150.

[0010]

[0020] The cathode current collector 110 may be a conductive film laminated with the cathode 120. The cathode current collector 110 may be, for example, an aluminum foil. Other forms of conductive foil are possible. The cathode 120 may be, for example, NCA (nickel-cobalt-aluminum oxide) or NCM (nickel-manganese-cobalt).

[0011]

[0021] The cathode 120 may have a first surface in direct contact with the cathode current collector 110, and the opposite surface of the cathode 120 may be in direct contact with the lithium gel separator layer 130. The lithium gel separator layer 130 may function as a solid electrolyte (in a gel form) to facilitate the movement of lithium ions between the cathode 120 and the anode current collector 150. The lithium gel separator layer 130 also acts as a separator to prevent direct electrical connection between the cathode 120 and the anode current collector 150. The lithium gel separator layer 130 may have features that further inhibit dendrite growth. The lithium gel separator layer 130 may be initially at least partially in a liquid state. After assembly, a process may be applied to convert the liquid to a gel state. Such a process may include pressure, heat, or both. Further details regarding the lithium gel separator layer 130 are provided in connection with FIG. 3A.

[0012]

[0022] The lithium gel separator layer 130 may have a first surface in direct contact with the cathode 120. A second surface of the lithium gel separator layer 130 opposite the first surface may be in direct contact with the anti-dendrite layer 140. The anti-dendrite layer 140 may have several key features. First, the anti-dendrite layer 140 may reduce the nucleation energy required for lithium ions to plate as lithium metal on the surface of the anode current collector 150 that is in direct contact with the anti-dendrite layer 140. By reducing the nucleation energy, lithium ions may be more likely to deposit directly on the anode current collector 150, rather than "pooling" or depositing on the lithium metal already plated on the anode current collector 150.

[0013]

[0023] A second major feature of the anti-dendrite layer 140 is that the amount of adhesion between the anti-dendrite layer 140 and the anode current collector 150 is less than the amount of adhesion between the anti-dendrite layer 140 and the lithium gel separator layer 130. The less adhesion between the surfaces of the anti-dendrite layer 140 and the anode current collector 150 encourages lithium to plate between the anti-dendrite layer 140 and the anode current collector 150 as opposed to between the lithium gel separator layer 130 and the anti-dendrite layer 140.

[0014]

[0024] The anti-dendrite layer 140 may be relatively thin. For example, the anti-dendrite layer 140 may be 0.05 μm to 10 μm. In some embodiments, the anti-dendrite layer 140 may be deposited as a film on the surface of the anode current collector 150. The anti-dendrite layer 140 may be made from one or more of the following materials: carbon black, acetylene back black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PvDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR). The anti-dendrite layer 140 may also be formed using an alloy of silver, zinc, gold, bismuth, and tin. The anti-dendrite layer 140 may be formed from a single type of material, although the anti-dendrite layer 140 may be formed using multiple materials as shown.

[0015]

[0025] The anode current collector 150 can have a first surface in contact with the anti-dendrite layer 140. The anode current collector 150 can function as both an anode and an anode current collector. In some embodiments, the anode current collector 150 is a conductive foil, such as a copper foil. In the absence of the anti-dendrite layer 140, the anode current collector 150 can exhibit a higher nucleation energy that tends to cause lithium to pool rather than deposit as a film during charging of the battery cell.

[0016]

[0026] FIG. 2 shows another embodiment of a layer stack 200 of an anode-free solid-state battery having multiple lithium gel separator layers and multiple anti-dendrite layers. In some embodiments, multiple sets of layers may be stacked together to increase the charge capacity of the battery cell. In the illustrated embodiment of FIG. 2, layers 110 to 150 are as detailed in connection with FIG. 1. In addition, an anti-dendrite layer 210 is stacked on the opposite side of the anode current collector 150 from the anti-dendrite layer 140. A second lithium gel separator layer 202 is in direct contact with the anti-dendrite layer 210. Additionally, a cathode 230 and a cathode current collector 240 are stacked against the lithium gel separator layer 220. Further layers may be added in the same manner as detailed in connection with FIG. 2. For example, under the cathode current collector 240, there may be another cathode, followed by another lithium gel separator layer, and so on. For example, multiple sets of layers may be added to increase the charge capacity of the battery cell. Although Figure 1 shows a single stack set and Figure 2 shows a double stack set, other embodiments may include more stacks, such as 16 or more. Once assembled, such layers may be sealed as part of a pouch-type battery cell.

[0017]

[0027] FIG. 3A illustrates an embodiment of a lithium gel separator layer formed using heat. FIG. 3B, detailed herein in parallel with FIG. 3A, illustrates an embodiment of a method of making a lithium gel separator layer. The lithium gel separator layer can function as a phase change electrolyte that can be used in a solid-state battery. A lithium gel separator layer, such as lithium gel separator layer 130, can include multiple sublayers and can be formed using heat. Pressure can also be used to increase the interfacial surface area between layers of the lithium gel separator layer. First, in block 350, a non-reactive scaffold can be formed. For example, the scaffold material 305 can be polyethylene (PE) or polyethylene oxide (PEO). The scaffold material 305 can be permeable such that a liquid, such as an electrolyte liquid, can permeate, inject, or otherwise be introduced into the scaffold material 305. The physical structure of the scaffold material 305 can create voids that can be filled with liquid. For example, the scaffold material 305 can have a porosity of 10% to 90% into which a liquid can be introduced. The particular physical structure may be a honeycomb structure, a spider web structure, or any other patterned or random porous physical structure that allows liquid to fill the void spaces within the scaffold material 305. The scaffold layer may be between 1 μm and 100 μm thick. In some embodiments, the scaffold layer is 15 μm thick.

[0018]

[0028] In block 355, a first adhesive layer may be attached to the non-reactive scaffold. In block 360, a second adhesive layer may be attached to the opposite side of the non-reactive scaffold. Thus, the scaffold material 305 may be located between two adhesive layers 310. Together, these three layers may form a dry separator layer 300 in which the electrolyte has not yet been introduced. Each of the adhesive layers 310 may include PvDF, PI, PAA, or CMC-SBR. Such materials may function as adhesive bonders. Thus, the adhesive layers 310 may act to increase the amount of adhesion between the scaffold material 305, the cathode 120, and the anti-dendrite layer 140. The amount of adhesion between the lithium gel separator layer 130 and the anti-dendrite layer 140, at least in part due to the adhesive layers, may be greater than the amount of adhesion between the anti-dendrite layer 140 and the anode current collector 150.

[0019]

[0029] In some embodiments, ceramics may be added to one or both adhesion layers that may improve lithium ion transport and help prevent dendrite formation. Such ceramics may include MgO, PZT, BaTiO3, SBT, BFO, LATSPO, LISICON, LICGC, LAGP, LLZO, LZO, LAGTP, LiBETI, LiBOB, LiTf, LiTF, LLTO, LLZP, LTASP, and LTZP. Each of the adhesion layers 310 may be 1-500 um thick. The use of ceramics in the adhesion layers may reduce ionic conductivity. The use of lithium ion conductor ceramics may still reduce ionic conductivity (compared to liquids), but may ensure higher ionic conductivity compared to other ceramics. However, the advantages of ceramics in preventing short circuits and reducing overall cell failure rates may outweigh the disadvantages of reduced ionic conductivity.

[0020]

[0030] At block 365, a liquid electrolyte mixture may be created. The liquid electrolyte mixture may include a lithium salt, a solvent, and an additive. The salt may be LIFSI, LITFSI, or LiPF6. The concentration of the salt may be 1.0 to 4.0 moles per liter. The lithium salt may enable the lithium liquid to function as an electrolyte. The solvent may be dimethyl carbonate (DMC), dimethoxyethane (DME), diethyl carbonate (DEC), dioxolane (DOL), bistrifluoroethyl ether (BTFE), ethyl methyl carbonate (EMC), or ethylene carbonate (EC). The solvent may function to dissolve the salt.

[0021]

[0031] The additives may include compounds within the lithium liquid that cause a liquid to gel transition upon heating. Typically, the additives include a polymer and a crosslinker. When heat, for example 60°C to 150°C, is applied to the additive, the crosslinker ignites, causing further polymerization of the polymer and the solvent. The lithium salt distributes uniformly throughout the solvent, so that when the gel is formed, the lithium salt distributes uniformly throughout the gel. The one or more additives may include CsPF6, FEC (fluoroethylene carbonate), polycarbonate (PC), or LiNO3. The additives may have a concentration of 0.01 to 4.0 moles per liter. The additives, including the polymer additive and the crosslinker additive, may be mixed into the lithium liquid before the lithium liquid permeates throughout the non-reactive framework.

[0022]

[0032] One possible combination of lithium salt and solvent may be 4M LiFSI dissolved in DME (to which additives may be added). Table 1 shows combinations of polymer additives, crosslinking additives, and relative concentrations of polymer additives and crosslinking additives that may be used.

[0023] [Table 1]

[0024]

[0033] In some embodiments, one or more additional additives may also function to reduce side reactions. The purpose of adding an additive may be to aid in the formation of LiF, i.e., a solid electrolyte interphase (SEI), which can prevent Li metal from having various side reactions.

[0025]

[0034] The lithium gel separator layer takes the form of dry separator layer 300, which may be laminated with other battery cell layers in place of lithium gel separator layer 130. Once assembly of the battery cell layers is complete and the battery cell is inserted into a housing (e.g., a pouch), liquid electrolyte may be applied, followed by the application of heat and pressure.

[0026]

[0035] At block 370, the liquid electrolyte mixture may be infiltrated into the non-reactive scaffold. Arrow 315 indicates that lithium liquid is infiltrated throughout the scaffold material 305 to create a lithium liquid infiltrated scaffold material 320. The lithium liquid may be infiltrated into the scaffold material that has been submerged under atmospheric pressure for a period of time, such as 6 hours to 24 hours. This step may be performed after the dry separator layer is assembled as part of the battery cell. The liquid electrolyte, which may be lithium liquid, may be comprised of a material that infiltrates voids within the scaffold material and then causes the lithium liquid to at least partially solidify, such as into a gel, after exposure to heat. Such an arrangement allows the lithium gel separator layer to be initially fabricated as a dry separator layer, and then, after the battery cell is housed within a housing (e.g., a pouch cell), the lithium liquid is infiltrated throughout the scaffold material and transitions to a gel. In some embodiments, pressure may also be applied, the purpose of which may be to increase the amount of contact at various interfaces within the stack.

[0027]

[0036] After the lithium liquid has been permeated throughout the scaffold 305 to create the lithium liquid permeated scaffold 320, block 375 may be performed where pressure, heat, or both may be applied, as indicated by arrow 325. For example, in some embodiments, pressure of 100 N / cm may be applied for a duration of 60-120 seconds. 2 Pressure may then be applied at room temperature with a force of 100-500 N / cm for a duration of 60-120 seconds. 2 The heat pressing process may be performed at a temperature of 100°C to 110°C with a pressure of 0.1 MPa. The heat applied to the lithium gel separator layer 301 may transition the lithium liquid permeated framework material 320 into a quasi-solid lithium gel layer 330. In some embodiments, pressure may aid this process or aid in increasing the interfacial surface area between the lithium gel separator layer and / or other layers of the battery cell. The lithium gel separator layer 302 may then be finally formed.

[0028]

[0037] To make such a battery cell, various methods can be followed. Figure 4 shows one embodiment of a method 400 for manufacturing a pouch-type battery cell including an anode-free solid-state battery having a lithium-gel separator layer and an anti-dendrite layer. In block 405, the anti-dendrite layer can be laminated onto the anode current collector. The anti-dendrite layer can be as detailed in connection with the anti-dendrite layer 140 of Figure 1. The anode current collector can be as detailed in connection with the anode current collector 150 of Figure 1.

[0029]

[0038] In block 410, a three-part lithium gel separator layer may be created. Initially, the lithium gel separator layer may be in the form of a dry separator layer. That is, as detailed in connection with FIG. 3A, liquid electrolyte, such as lithium liquid, has not yet been infused into the scaffold layer. In other embodiments, the scaffold material in block 410 is liquid permeated. The lithium gel separator layer, in which lithium liquid may be present or may not yet have been introduced, may be laminated onto the anti-dendrite layer in block 415. The amount of adhesion between the lithium gel separator layer and the anti-dendrite layer may be greater than the amount of adhesion between the anti-dendrite layer and the anode current collector. In some cases, the amount of adhesion between the lithium gel separator layer and the anti-dendrite layer may be greater than the amount of adhesion between the anti-dendrite layer and the anode current collector after the heat and pressure of block 430.

[0030]

[0039] At block 420, a cathode layer may be laminated onto the lithium gel separator layer (wherein the gel is still liquid or has not yet been introduced into the scaffold material). At block 425, a cathode collector layer may be laminated onto the cathode layer. In some embodiments, block 425 may be performed, after which the integrated cathode layer and cathode current collector layer may be laminated onto the lithium gel separator layer (wherein the gel is still liquid or has not yet been introduced into the scaffold material) at block 420.

[0031]

[0040] It should be understood that blocks 405-425 may be repeated multiple times to create a multi-layer stack of solid-state battery cells. For example, a 16-layer set may be created in a stack set similar to that detailed in connection with Figure 2. Such an arrangement allows the anode and cathode current collectors to contact the anti-dendrite layer and the cathode on both sides, respectively.

[0032]

[0041] In block 430, one or more layer stacks may be packaged into a pouch cell. In this block, the lithium liquid (or other form of liquid electrolyte) may still be in liquid form, assuming it was introduced in block 410. The layer stack may be vacuum packed in the pouch cell to remove excess air. The pouch cell may be made of a flexible material, such as plastic, which may allow the pouch to expand and compress. If the lithium liquid did not permeate the entire skeletal layer in block 410, the lithium liquid may be introduced into the pouch cell while (or before or after) packaging is taking place in block 432. The lithium liquid may then permeate into the skeletal layer of the dry separator layer.

[0033]

[0042] At block 435, one or more processes of heat, pressure, or both may be applied to the packaged pouch cell. This process may perform multiple functions: 1) block 435 may increase the amount of physical contact between adjacent layers of the battery cell, 2) block 435 may convert the lithium liquid into a lithium gel, and 3) block 435 may create an adhesion between the anti-dendrite layer and the lithium gel layer that is greater than the amount of adhesion between the anti-dendrite layer and the anode current collector. For example, in some embodiments, a pressure of 80-120 N / cm is first applied for a duration of 60-120 seconds. 2 Pressure may then be applied at room temperature with a force of 100-500 N / cm for a duration of 60-120 seconds. 2 The heat pressing process may be carried out at a temperature of 80°C to 130°C with a force of 0.1 to 1.0 MPa.

[0034]

[0043] At block 440, the pouch cell may be placed into a jig press (or other mechanical device that applies pressure to the pouch cell). The jig press may be used to apply long term pressure to the SSB pouch cell. In some embodiments, multiple SSB pouch cells are stacked and then compressed using the jig press. While in the jig press, the SSB pouch cell may be repeatedly charged and discharged. The SSB pouch cell may be used to power a vehicle or other form of electrically powered device.

[0035]

[0044] As an example of an SSB that may be manufactured according to FIG. 2 and by method 400, an SSB pouch cell may be made that includes 16 layer sets and is approximately 65 mm by 65 mm. For a given layer, at 0% SOC (state of charge), there is a thickness of 3.3 mm. At 100% SOC, there is a thickness of 3.64 mm, which represents approximately a 10% increase caused by expansion. Overall cell performance may be 4520 mAh with an average voltage of 3.79 V. At 100% SOC, the energy density (by volume) may be 1122 Wh / L and the energy density (by weight) may be 432 Wh / Kg.

[0036]

[0045] The above embodiments are directed to making planar layers of battery cells. Such layers may be used in pouch-type battery cells. In other embodiments, cylindrical battery cells may be made as detailed in connection with Figures 5 and 6. Such cylindrical battery cells may have the same stacking as detailed in connection with Figures 1-3, although the process for making the cylindrical cells may be different. Further details regarding such embodiments are provided in connection with Figures 5 and 6.

[0037]

[0046] 5 illustrates one embodiment of a cylindrical battery press system 500. The cylindrical battery press system 500 may include a compression mechanism 510, a heating element 520, a cushioning material 530, a cylindrical pouch battery cell (also referred to as a "battery cell") 540, a temperature sensor 550, a support structure 560, and a platform 570. An embodiment of a cylindrical battery press system and related systems is described in detail in U.S. Patent Application Serial No. 16 / 412,338, filed May 14, 2019, entitled "Isostatic Press Devices and Processes for Cylindrical Solid-State Batteries," the entire disclosure of which is incorporated herein by reference for all purposes. Other embodiments of a system for isostatically pressing cylindrical battery cells are detailed in U.S. patent application Ser. No. 16 / 217,010, entitled "Hydraulic Isostatic Press Processes for Solid-State Batteries," filed Dec. 11, 2018, the entire disclosure of which is also incorporated by reference herein for all purposes.

[0038]

[0047] The compression feature 510 may be generally cylindrical in shape and may have a cross section similar to a halo. There may be a gap along the curved sidewall of the compression feature 510. On either side of the gap is an edge 511 and an edge 512. By moving the edge 511 towards the edge 512, a volume within the compression feature 510 may be reduced. Thus, as the edge 511 moves away from the edge 512, the volume within the compression feature is larger, allowing the cushioning and / or the battery cells 540 to be placed. As the edge 511 moves towards the edge 512, the volume within the compression feature 510 is smaller, thus applying pressure to the cushioning 530 and through the cushioning 530 to the battery cells 540.

[0039]

[0048] The battery cells 540 may be cylindrical jelly roll battery cells, similar to the embodiment of Figures 1-3. The cylindrical jelly roll battery cells may be (initially) housed inside a pouch that may be compressed using a cylindrical battery press system 500. After being compressed and heated using the cylindrical battery press system 500, as detailed in method 600 of Figure 6, the cylindrical jelly roll battery cells may be removed from the pouch and placed into a cylindrical canister.

[0040]

[0049] Compression mechanism 510 may be formed from a semi-rigid material such as a hard rubber, plastic, or metal layer. Compression mechanism 510 may be partially deformed by pushing or pulling edge 511 toward edge 512. In some embodiments, edge 512 may be fixed to support structure 560. Edge 511 may be connected to an extension, such as a metal bar, that allows a user to manually push or pull the metal bar to move edge 511 toward edge 512. In other embodiments, a hydraulic pump or electric motor may be used to move edge 511 toward edge 512.

[0041]

[0050] The cushioning material 530 may be wrapped around the battery cells 540. The cushioning material 530 may be a semi-rigid material such as heat resistant rubber. In some embodiments, the cushioning material 530 may be a rubber or other form of flexible skin that is filled with liquid. The cushioning material 530 may be generally halo shaped when viewed in cross section. The halo shape defines a cavity at its center within which the battery cells may be placed. The cushioning material 530 may act to transfer the pressure applied by the compression mechanism 510 to the battery cells 540. The cushioning material 530 may help distribute the pressure applied by the compression mechanism 510 so that the pressure applied to the curved side walls of the battery cells 540 is uniform or nearly uniform. In some embodiments, the cushioning material 530 is first wrapped around the battery cells 540. In some embodiments, the cushioning material 530 may be a sheet of cushioning material into which the battery cells are wrapped. Thus, the jelly roll battery cells may then reside within a jelly roll of cushioning material 530. The cushioning material 530 may be installed along with the compression mechanism 510.

[0042]

[0051] Between the cushioning material 530 and the compression mechanism 510, there may be a heating element 520. The heating element 520 may be generally cylindrical and may have gaps along its curved sidewalls that match the gaps of the compression mechanism 510. The heating element 520 may be a resistive heater such that heat is generated when a current is applied to the heating element 520. In some embodiments, the heating element 520 is capable of heating up to 250° C. The amount of heat output by the heating element 520 may be controlled based on the output of a temperature sensor 550. The temperature sensor 550 may be located between the battery cell 540 and the cushioning material 530. Thus, the temperature sensor 550 may indicate a temperature at an outer surface of the battery cell 540. In some embodiments, it may be desirable for the battery cell 540 to be heated to between 80° C. and 120° C. Applying a higher temperature using the heating element 520 may allow the battery cell 540 to be heated to between 80° C. and 120° C. more quickly at its surface. An external heating controller (not shown) may receive the temperature measurements from the temperature sensor 550 and control the amount of heat generated by the heating element 520 .

[0043]

[0052] The edge 512 may be fixed to the support structure 560, which in turn is fixed to the platform 570, while the edge 511 may remain free. By leaving the edge 511 free from the support structure 560 and the platform 570, the edge 511 may be moved towards the edge 512, which may result in a slight deformation of the compression mechanism 510. When the force is stopped from being applied to the edge 511, the compression mechanism 510 may expand to return to its natural shape, and pressure may cease to be applied to the battery cell 540. It should be understood that the force applied to the edge 511 may be applied near the edge 511, and not necessarily exactly on the edge 511. However, the closer such force is applied to the edge 511, the more evenly the pressure applied to the cushioning material 530 may be distributed. Similarly, it should be understood that the edge 512 may be fixed directly to the support structure 560, or more precisely, a portion of the compression mechanism 510 near the edge 512 may be fixed to the support structure 560. Again, the closer the portion of the compression mechanism 510 is to the edge 512 that is secured to the support structure 560, the more evenly the pressure applied to the cushioning material 530 can be distributed.

[0044]

[0053] Various methods may be performed to make a cylindrical battery cell. Figures 6A and 6B show one embodiment of a method to make a cylindrical dendrite-prevented anode-free solid-state battery. In blocks 605-620, various steps may be performed to make a layer stack similar to that presented in and described in connection with Figure 1. In other embodiments, blocks 605-620 may be performed to make a stack set as detailed in connection with Figure 2. That is, blocks 605-620 may be performed multiple times for two or more (e.g., 3-20) layer sets.

[0045]

[0054] Blocks 605-620 show one possible embodiment of how multiple layers may be stacked together. In other embodiments, blocks 605-620 may be ordered differently. In block 605, a cathode layer may be attached to a cathode current collector layer. The cathode current collector layer may be an aluminum foil and the cathode may be, for example, NCA (nickel-cobalt-aluminum oxide) or NCM (nickel-manganese-cobalt). The cathode layer may be deposited on the cathode current collector layer or the cathode current collector layer may be deposited on the cathode layer.

[0046]

[0055] In block 610, an anti-dendrite layer may be deposited on or otherwise attached to the anode current collector layer. The anode current collector layer may be copper, and the anti-dendrite layer may be carbon black, acetylene back black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PvDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR). The anti-dendrite layer may also be formed using an alloy of silver, zinc, gold, bismuth, and tin. The anti-dendrite layer may act to reduce the nucleation energy for lithium ions to deposit on the surface of the anode current collector layer.

[0047]

[0056] At block 615, a dry separator layer, such as dry separator layer 300, may be attached to or positioned between a cathode layer or an anti-dendrite layer. The dry separator layer may include two adhesive layers and a scaffolding material as detailed in connection with dry separator layer 300. At block 620, a laminate stack may be created that includes the dry separator layer laminated between the cathode and the anti-dendrite layer. The laminate stack may include at least a dry separator layer, an anti-dendrite layer, an anode current collector layer, a cathode layer, and a cathode current collector layer (as shown in FIG. 1 with the dry separator layer instead of the lithium gel separator layer).

[0048]

[0057] In block 625, the laminate stack may be rolled on itself multiple times to create a jelly-roll type battery cell. When the layers are rolled together, a generally cylindrical rolled laminate stack may be created. In block 630, the rolled laminate stack may be inserted into a compressible flexible pouch. The pouch may act as a temporary housing for the battery cell during part of the manufacturing process. Prior to sealing the pouch, an electrolyte solution may be injected or added into the pouch. The electrolyte solution may be lithium liquid as detailed in connection with FIG. 3A. The injection of the lithium liquid may cause the skeletal material of the dry separator layer to be permeated with the lithium liquid and become a lithium liquid permeated skeletal material, such as the lithium liquid permeated skeletal material 320. As part of block 635, the pouch may be sealed with any air removed from it.

[0049]

[0058] At block 640, pressure may be applied to the pouch. Pressure may be applied using a system similar to cylindrical battery press system 500. Before pressure is applied, a temperature probe may be inserted within the cylindrical battery press system so that it is adjacent to the exterior surface of the pouch. Pressure may then be applied by the cylindrical battery press system, either manually or using an electric or hydraulic embodiment. The applied pressure may be between 100 kPa and 100 MPa. In some embodiments, pressure is applied for a period of between 30 seconds and 1 hour.

[0050]

[0059] Heat may be applied in block 645, which may occur simultaneously with block 640 or at least partially overlapping in time with block 640. The amount of heat applied may be between 150°C and 250°C. The temperature of the pouch may be monitored using a temperature probe. Heat may be applied until the battery cell is between 60°C and 150°C for a period of time, such as 30 seconds to 1 hour. The pressure, heat, or both may transition the lithium liquid that permeates the skeletal layer into a quasi-solid lithium gel layer. Thus, no liquid remains in the pouch. Thus, the battery cell is a solid-state (including gel) battery cell.

[0051]

[0060] The heat and pressure applied in blocks 640 and 645 may additionally or alternatively increase the amount of surface area contact between one or more of the layers of the battery cell. Additionally or alternatively, the heat and pressure may increase adhesion between two or more of the layers of the battery cell.

[0052]

[0061] At block 650, the cylindrical jelly roll that has been exposed to heat and pressure may be removed from the pouch. There may be no liquid present since the liquid has transitioned to a gel in the skeletal layer. The cylindrical jelly roll may be inserted into a cylindrical battery cell canister. The cylindrical battery cell canister may be rigid or semi-rigid. In some embodiments, the cylindrical battery cell canister may be metallic. The cylindrical battery cell canister may exert pressure on the cylindrical jelly roll as it expands. For example, when the battery cell is charged at block 660, lithium deposition on the anode current collector may cause the battery to expand 0.5% to 3% in diameter. The pressure exerted by the sidewalls of the cylindrical battery cell canister may help control the amount of expansion and help keep the layers of the battery cell in contact with each other. At block 660, the battery cell may be repeatedly charged and discharged to power an electric device, such as an electric vehicle (EV). A cylindrical battery manufactured according to method 600 can be charged to 7559 Ah and discharged to 6229 Ah, thus exhibiting an initial coulombic efficiency of 82.4%.

[0053]

[0062] When lithium deposits on the anode current collector during charging, it may tend to deposit in puddles rather than a generally even film. The amount of contact that exists between the deposited lithium and the anode current collector may be small, resulting in a small electrical connection between the deposited lithium and the anode current collector. Having a small or weak electrical connection between the deposited lithium and the anode current collector may cause the impedance of the battery cell to be high. High impedance may result in poor performance of the battery cell: a battery with low internal resistance may be able to deliver a large amount of current on demand. In some applications, such as use in electric vehicles (EVs), the ability to deliver current quickly may greatly affect performance, such as the EV's ability to accelerate. If a battery cell has a high internal resistance, the current flowing through the battery cell may cause the battery to heat up, which may damage the battery cell.

[0054]

[0063] In some embodiments, there may be an additional layer in the layer stack of the anode-free solid-state battery. The additional layer may be located between the anti-dendrite layer and the anode current collector. This layer may be referred to as an interfacial bonding layer. The interfacial bonding layer may promote the formation of lithium deposits with high surface contact between the interfacial bonding layer and the lithium deposits. The interfacial bonding layer may have a large amount of contact with both the anode current collector and the deposited lithium, thereby reducing the internal resistance of the battery cell. Such an interfacial bonding layer may be added to any of the embodiments as detailed in connection with Figures 1-6 or as detailed in connection with Figures 7-10.

[0055]

[0064] The interface layer may be made of a conductive agent and a binder. In some embodiments, the interface layer may be 30%-99% conductive agent, and the remainder of the interface bonding layer may be a binder (1%-70%). FIG. 7 shows an embodiment of a layer stack 700 of an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interface bonding layer. The layer stack 700 may be as detailed in connection with FIG. 1, but an interface bonding layer 710 may be present between the anode current collector 150 and the anti-dendrite layer 140. The interface bonding layer 710 may be in direct contact with the anti-dendrite layer 140 on a first surface side and in direct contact with the anode current collector 150 on a second opposite surface side.

[0056]

[0065] To facilitate deposition of lithium metal on the interfacial bonding layer 710, the interfacial bonding layer 710 may have a first amount of adhesion with the anode current collector 150 that is greater than a second amount of adhesion between the anti-dendrite layer 140 and the interfacial bonding layer 710 or a third amount of adhesion between the anti-dendrite layer 140 and the lithium gel separator layer 130. The interfacial bonding layer 710 may have a thickness between 0.05 μm and 5 μm. The interfacial bonding layer may have a density between 0.1 and 2.0 grams per cubic centimeter.

[0057]

[0066] The interface bonding layer 710 may use carbon as a conductive agent mixed with a binder (PvDF, SBR-CMC, PAA) and metal particles such as Bi, Sn, Ag, Au, Pt, etc. More specifically, acetylene black or carbon black may be used as the conductive agent. The individual carbon particles may be spherical particles of 3 nm to 20 nm. Possible types of bonders include PvDF, SBR-CMC, and PAA.

[0058]

[0067] The impedance or resistance of the battery cell of Figure 7, measured between terminals 720 and 730, may be significantly reduced due to the presence of interfacial bonding layer 710, as compared to an embodiment such as Figure 1, in which there is no interfacial bonding layer 710. As an example, an embodiment of a battery cell without an interfacial bonding layer may have an impedance of 0.85 ohms, whereas with an interfacial bonding layer present between the anode current collector and the anti-dendrite layer, the impedance may be 0.05 ohms.

[0059]

[0068] 8 illustrates one embodiment of a layer stack 800 of an anode-free solid-state battery showing the relative amount of adhesion between the various layers. One of the key aspects of the layer stack 700 of FIG. 7 may be that the relative amount of adhesion between the layers encourages lithium metal to plate between the anti-dendrite layer 140 and the interfacial bonding layer 710 during the charging process.

[0060]

[0069] Interface 801 between lithium gel separator layer 130 and anti-dendrite layer 140 may have a first amount of adhesion. Interface 802 between anti-dendrite layer 140 and interfacial bonding layer 710 may have a second amount of adhesion. Interface 803 between interfacial bonding layer 710 and anode current collector 150 may have a third amount of adhesion. Interface 802 may have less adhesion than interface 801 or interface 803 to encourage lithium to plate at interface 802. Stated another way, the second amount of adhesion may be greater than the first amount of adhesion or the third amount of adhesion.

[0061]

[0070] 9 shows an embodiment 900 of a layer stack of an anode-free solid-state battery in which lithium ions migrate and are deposited on the interfacial bonding layer. In the embodiment 900, the battery cell is being charged. Charging causes lithium ions to migrate from the cathode 120, through the lithium gel separator layer 130, through the anti-dendrite layer 140, as shown by arrow 905, and plate as lithium metal layer 910 between the anti-dendrite layer 140 and the interfacial bonding layer 710. The anti-dendrite layer 140 can help inhibit the growth of dendrites that may penetrate the lithium gel separator layer 130. Thus, the interfacial bonding layer 710 may be used in conjunction with the anti-dendrite layer 140.

[0062]

[0071] The presence of the lithium metal layer 910 may cause the battery cell to expand. During a discharge cycle, lithium ions may migrate from the lithium metal layer 910 to the cathode 120. As the battery cell is discharged and the lithium ions migrate to the cathode layer 120, the expansion within the battery cell may decrease.

[0063]

[0072] 10 illustrates one embodiment of a method 1000 for manufacturing a pouch-type battery cell including a solid-state battery having a lithium-gel separator layer, an anti-dendrite layer, and an interfacial bonding layer. It should be understood that method 1000 can be adapted such that the interfacial bonding layer can be manufactured as part of a cylindrical battery cell according to blocks of method 600 of FIGs. 6A and 6B.

[0064]

[0073] In block 1005, an interfacial bonding layer may be deposited on the anode current collector, which may be as detailed in connection with anode current collector 150 of Figure 1. Block 1005 may include a conductive material, such as acetylene black, being mixed with a bonder and deposited on the anode current collector.

[0065]

[0074] In block 1010, a three-part lithium gel separator layer may be created. Initially, the lithium gel separator layer may be in the form of a dry separator layer. That is, as detailed in connection with FIG. 3A, a liquid electrolyte such as lithium liquid has not yet been injected into or has not yet permeated the entire scaffold layer. In other embodiments, the scaffold material is liquid permeated. In block 1020, an anti-dendrite layer may be laminated onto the lithium gel separator layer, in which lithium liquid (or another liquid electrolyte) may or may not be present. The anti-dendrite layer may be as detailed in connection with anti-dendrite layer 140 of FIG. 1. In some cases, the amount of adhesion between the lithium gel separator layer and the anti-dendrite layer may be greater than the amount of adhesion between the anti-dendrite layer and the interface bonding layer.

[0066]

[0075] At block 1025, a cathode layer may be laminated onto the lithium gel separator layer (wherein the gel is still liquid or not yet present). At block 1030, a cathode collector layer may be laminated onto the cathode layer. In some embodiments, block 1030 may be performed, after which the combined cathode layer and cathode current collector layer may be laminated onto the lithium gel separator layer at block 1025.

[0067]

[0076] In block 1032, the anti-dendrite layer previously laminated onto the lithium gel separator layer may have an opposing layer laminated onto the interfacial bonding layer. The lamination of the anti-dendrite layer and the interfacial bonding layer may result in relatively little adhesion being present between the layers. The anti-dendrite layer may result in an interface having less adhesion with the interfacial bonding layer than the interfacial bonding layer does with the anode current collector. The amount of adhesion may be controlled by adjusting the ratio of binder to active conductive material in the interfacial bonding layer. For example, PvDF may be used as the binder and Ketjen Black as the active material in a ratio of 97% Ketjen Black to 3% PvDF. In other embodiments, the percentage of Ketjen Black is 95% to 98%.

[0068]

[0077] It should be understood that blocks 1005-1030 may be repeated multiple times to create a multi-layer stack of solid-state battery cells. For example, a 16-layer set may be created in a stack set similar to that detailed in connection with Figure 2, with the addition of an interfacial bonding layer. Such an arrangement allows the anode and cathode current collectors to contact the anti-dendrite layer and the cathode on both sides, respectively.

[0069]

[0078] In block 1035, one or more layer stacks may be packaged into a pouch cell. In this block, the lithium liquid (or other form of liquid electrolyte) may still be in liquid form, assuming it was introduced in block 1015. The layer stack may be vacuum packed in the pouch cell to remove excess air. The pouch cell may be made of a flexible material, such as plastic, which may allow the pouch to expand and compress. If the liquid electrolyte, such as lithium liquid, did not permeate the entire skeletal layer in block 1015, the liquid electrolyte may be introduced into the pouch cell at the time (or before or after) packaging is taking place in block 1040. The lithium liquid may then permeate into the skeletal layer of the dry separator layer.

[0070]

[0079] In block 1045, one or more processes of heat, pressure, or both may be applied to the packaged pouch cell. This process may perform multiple functions: 1) block 1045 may increase the amount of physical contact between adjacent layers of the battery cell, 2) block 1045 may convert the liquid electrolyte (e.g., lithium liquid) to a lithium gel, and 3) block 1045 may help create an adhesion between the interfacial bonding layer and the anode current collector that is greater than the amount of adhesion between the anti-dendrite layer and the interfacial bonding layer. For example, in some embodiments, a pressure of 80-120 N / cm may be applied for a duration of 60-120 seconds. 2 Pressure may be applied at room temperature with a force of 100-1000 N / cm for a duration of 60-2400 seconds. This part of the process may increase the amount of contact that exists at the interface of one or more of the layers of the battery cell. 2 The heat pressing process may be carried out at a temperature of 50°C to 130°C with a force of 0.1 MPa.

[0071]

[0080] At block 1050, the pouch cell may be placed into a jig press (or other mechanical device that applies pressure to the pouch cell). The jig press may be used to apply long term pressure to the SSB pouch cell. In some embodiments, multiple SSB pouch cells are stacked and then compressed using the jig press. While in the jig press, the SSB pouch cell may be repeatedly charged and discharged. The SSB pouch cell may be used to power a vehicle or other form of electrically powered device.

[0072]

[0081] The methods, systems, and devices described above are examples. Various configurations may omit, substitute, or add various procedures or components, as appropriate. For example, in alternative configurations, the methods may be performed in an order different from that described, and / or various steps may be added, omitted, and / or combined. Also, features described with respect to particular configurations may be combined in various other configurations. Different aspects and elements of the configurations may be combined in a similar manner. Also, because technology evolves, many of the elements are examples and do not limit the scope of the disclosure or claims.

[0073]

[0082] In the above description, specific details are provided to provide a thorough understanding of the example configurations (including the embodiments). However, the configurations can be practiced without these specific details. For example, well-known processes, structures, and techniques are shown without unnecessary detail to avoid obscuring the configurations. This description is merely to provide an example configuration and is not intended to limit the scope, applicability, or configuration of the claims. Rather, the description of the configurations above provides a person skilled in the art with an explanation of the enabling requirements for implementing the described technology. Various changes can be made with respect to the function and arrangement of elements without departing from the spirit or scope of the present disclosure.

[0074]

[0083] Also, the configurations may be described as processes that are depicted as flow diagrams or block diagrams. Although each may describe operations as sequential processes, many of these operations may occur in parallel or simultaneously. Additionally, the order of operations may be rearranged. A process may have additional steps not included in the figures.

[0075]

[0084] While several example configurations have been described, various modifications, alternative constructions, and equivalents may be used without departing from the spirit of the disclosure. For example, the above elements may be components of a larger system in which other rules may take precedence over or modify the application of the invention. Also, some steps may be initiated before, during, or after the above elements are considered.

Claims

1. 1. A dendrite-preventing anode-free solid-state battery, comprising: A cathode layer; and an anode current collector layer; a lithium gel separator layer between the cathode layer and the anode current collector layer; an anti-dendrite layer located between the lithium gel separator layer and the anode current collector layer, the anti-dendrite layer preventing the formation of dendrites; Including, The lithium gel separator layer is A first adhesive layer; A second adhesive layer; and a lithium gel layer located between the first adhesive layer and the second adhesive layer; 13. A dendrite-preventing anode-free solid-state battery comprising:

2. 10. The anti-dendrite anode-free solid-state battery of claim 1, wherein the lithium gel layer comprises a framework material, a salt, a solvent, and at least one additive.

3. 3. The anti-dendrite anode-free solid state battery of claim 2, wherein the at least one additive comprises a polymer and a crosslinker.

4. 3. The anti-dendrite anode-free solid state battery of claim 2, wherein the first adhesion layer and the second adhesion layer comprise a lithium conductor ceramic.

5. 10. The anti-dendrite anode-free solid-state battery of claim 1, wherein the presence of the anti-dendrite layer reduces the nucleation barrier for energy for lithium ions to deposit on the anode current collector layer.

6. 6. The anti-dendrite anode-free solid state battery of claim 5, wherein the anti-dendrite layer is 0.05 micrometers to 10 micrometers thick.

7. 7. The anti-dendrite anode-free solid-state battery of claim 6, wherein the anti-dendrite layer comprises one or more materials selected from the group consisting of carbon black, acetylene black, Ketjen black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR).

8. 8. The anti-dendrite anode-free solid state battery of claim 7, wherein a first amount of adhesion between the anti-dendrite layer and the anode current collector layer is less than a second amount of adhesion between the anti-dendrite layer and the lithium gel separator layer.

9. 9. The dendrite-prevented anode-free solid state battery of claim 8, wherein the anode current collector layer is copper.

10. 10. The anti-dendrite anode-free solid state battery of claim 1 further comprising an aluminum cathode current collector.

11. 1. A method for making a dendrite-preventing anode-free solid-state battery, comprising: depositing an anti-dendrite layer on the anode current collector layer; Producing a lithium gel separator layer; depositing a cathode current collector layer onto the cathode layer; laminating the lithium gel separator layer between the anti-dendrite layer and the cathode layer, thereby creating a laminated cell stack of the cathode current collector layer, the cathode layer, the lithium gel separator layer, the anti-dendrite layer, and the anode current collector layer; packaging the laminated battery stack into a flexible pouch cell; applying heat and pressure to the laminated battery stack within the flexible pouch cell; Including, Producing the lithium gel separator layer comprises: Attaching a first adhesive layer to a scaffold; attaching a second adhesive layer to the scaffold; Permeating the scaffold with a liquid electrolyte; A method for making a dendrite-preventing anode-free solid-state battery comprising:

12. 12. The method of making an anti-dendrite anode-free solid-state battery according to claim 11, wherein the liquid electrolyte comprises a lithium salt, a solvent, and at least one additive.

13. 13. The method of making an anti-dendrite anode-free solid state battery according to claim 12, wherein the at least one additive comprises a polymer and a cross-linking agent.

14. 14. The method of making a dendrite-preventing anode-free solid-state battery of claim 13, wherein the application of heat causes the liquid electrolyte to become a gel.

15. 12. The method of making an anti-dendrite anode-free solid-state battery as claimed in claim 11, wherein the presence of the anti-dendrite layer reduces the nucleation barrier for energy for lithium ions to deposit on the anode current collector layer.

16. 16. The method of making an anti-dendrite anode-free solid state battery according to claim 15, wherein the anti-dendrite layer is 0.05 micrometers to 10 micrometers thick.

17. compressing the flexible pouch cell in a jig press; charging and discharging the laminated battery stack in the jig press; 12. The method of making the dendrite-prevented anode-free solid-state battery of claim 11, further comprising:

18. 12. The method of making an anti-dendrite anode-free solid-state battery as claimed in claim 11, wherein the anti-dendrite layer comprises one or more materials selected from the group consisting of carbon black, acetylene black, ketjen black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), and carboxymethyl cellulose styrene butadiene rubber (CMC-SBR).

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2020526893A

  • Lithium secondary battery

    WO2019004699A1